The Economics of Labor and Collective Bargaining - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "The Economics of Labor and Collective Bargaining" by William H. Miernyk.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z